A comprehensive review of 46 exercise treatment studies in fibromyalgia (1988–2005) - Winters-Stone Kerri; Adams Dianne; Jones Kim; Burckhardt Carol S (Health and Quality of Life Outcomes, 2006)
Abstract The purpose of this review was to: (1) locate all exercise treatment studies of fibromyalgia (FM) patients from 1988 through 2005, (2) present in tabular format the key details of each study and (3) to provide a summary and evaluation of each study for exercise and health outcomes researchers. Exercise intervention studies in FM were retrieved through Cochrane Collaboration Reviews and key word searches of the medical literature, conference proceedings and bibliographies. Studies were reviewed for inclusion using a standardized process. A table summarizing subject characteristics, exercise mode, timing, duration, frequency, intensity, attrition and outcome variables was developed. Results, conclusions and comments were made for each study. Forty-six exercise treatment studies were found with a total of 3035 subjects. The strongest evidence was in support of aerobic exercise a treatment prescription for fitness and symptom and improvement. In general, the greatest effect and lowest attrition occurred in exercise programs that were of lower intensity than those of higher intensity. Exercise is a crucial part of treatment for people with FM. Increased health and fitness, along with symptom reduction, can be expected with exercise that is of appropriate intensity, self-modified, and symptom-limited. Exercise and health outcomes researchers are encouraged to use the extant literature to develop effective health enhancing programs for people with FM and to target research to as yet understudied FM subpopulations, such as children, men, older adults, ethnic minorities and those with common comorbidities of osteoarthritis and obesity.